Komunikasi bisnis. Bisnis sebagai proses komunikasi. Komunikasi sebagai kegiatan bisnis - PANUJU, Redi (GRAMEDIA, 1995)
Komunikasi bisnis. Bisnis sebagai proses komunikasi. Komunikasi sebagai kegiatan ....